General conditions and main problems of implementing the Basel III international standards for the banking system of Kazakhstan (Journal of Economic Research & Business Administration, 2017)
Based on the lessons of the financial crisis of 2008-2009, the Basel Committeeof Banking Supervision launched a revision of its requirements oncapital sufficiency. In this connection, Basel III document was adopted by theBasel committee of banking supervision. Currently, the community is havingmany questions about the standards and their application, the timing of the introductionof Basel 3, the possible consequences of these changes. Therefore,this leads to the relevance of this research.The paper considers the approachesof the National Bank of the Republic of Kazakhstan toward the capital adequacyrequirements and conservation buffer for the second-tier banks in theprocess of upcoming reform of banking regulation and international settlementknown as “Basel-III”. Basic provisions of Basel III as well as the principlesof integration of the country’s banking system to the Basel agreement arediscussed. In particular, the author focuses on such principles as tighteningof capital adequacy requirements, establishment of single liquidity standards,and additional standards for the global systematically important financial institutions.The paper provides an overview of possible impact that Basel IIIstandards might exert on the banking system operation, economic growth andfinancial stability. Further, the author conducts a comparative analysis of capitaladequacy requirements and conservation buffer established by the regulatorsin such countries as Kazakhstan, Russia, and Singapore.